Socio-environmental vulnerability of water in the estuary of the metropolitan region of Santos (Brazil) - Martins, Fernando L.C.; Giordano, Fabio; Barrella, Walter (Quaestiones Geographicae, 2021)
Santos and São Vicente Estuarine Complex (SSEC) is a densely populated coastal area that houses the main port in Latin America and the most prominent Brazilian industrial complex. Irregular occupations in preservation areas result in a disorderly increase in population, with negative social and environmental impacts. We evaluated the average annual growth of 74 slums occurring in this area and variations in water quality from 2005 to 2018. We monitor the growth of the occupied areas and estimate their respective populations. The average annual population growth was over 6% per year (p.a.). Invasions of new areas and verticalisation of already occupied areas represent 85% of the growth seen. The monthly polluting loads exceeded 450 tonnes or 2,086,000 m3, compromising the waters and local and regional public health. We strongly recommend re-urbanising the area using the resource savings caused by water loss to reduce the risks of ecosystem degradation, damage to health and disease spread.